IMPLEMENTATION OF AL-MA'UN THEOLOGY: MEASURING MUHAMMADIYAH SOCIAL ACTION AT THE CENTER OF WAKATOBI WORLD'S CORAL TRIANGLE - Muhammad Alifuddin; Fitriah M. Suud; Moh. Toriqul Chaer (UIN Raden Mas Said Surakarta, 2021)
This study aims to describe the social action of the Muhammadiyah movement in Wakatobi, Southeast Sulawesi. It is qualitative research, with the data obtained through in-depth interviews with key informants, field observations, and related documents, then analyzed using the Miles and Huberman paradigm. The results conclude that the social action of the Muhammadiyah movement in Wakatobi was in the form of educational services for a marginalized community in Bajo Mola and Kaledupa is still only a moral appeal. An appeal to the community to jointly educate and empower the community. From the analysis conducted, especially on the steps of a movement, the social action of the Muhammadiyah movement has not fully implemented the concept of Al-ma’un theology. Social service in education only touches the charitable dimension, while the empowerment aspect has not received attention. This reality is closely related to the resource capacity of Muhammadiyah Wakatobi. To fulfill the ideal concept of Al-Ma’un’s theology, Muhammadiyah in Wakatobi should build intensive collaboration and communication with various institutions and involve the local community.